Analysis of Internet searches using Google Trends to measure interest in sun protection and skin cancer in selected South‐East Asian populations. Issue 2 (11th October 2019) - Kwan, Zhenli; Yong, Shin Shen; Robinson, Suganthy
Abstract: Background: Analysis of Internet search trends has been performed to evaluate interest in sun protection, artificial tanning, and skin cancers among the public, particularly in Western countries. This observational study aimed to investigate the relative popularity of search terms relating to sun protection, sunburn, skin cancers, and tanning used in Google Trends® in three South‐East Asian countries (Malaysia, Singapore, and Indonesia). Methods: The relevant search terms were queried using the Google Trends® in each location and worldwide. The search volume indices were compared between locations and over a time period from January 1, 2004, to January 31, 2019. Correlations between "sunblock" and "sunburn" as well as "sunblock" and search terms relating to skin cancers ("skin cancer, " "melanoma, " "basal cell carcinoma, " and "squamous cell carcinoma") were evaluated. Results: The favored search term relating to sun protection in this region was "sunblock" despite the term itself being a misnomer. The relative popularity of searches for "sunblock" also showed an increase over time and was generally higher compared with interest in sunburn, skin cancers, and artificial tanning practices. Positive correlations were noted between "sunblock" and "sunburn" in Malaysia and "sunblock" and "melanoma" in Singapore. Conclusion: Insights into search trends may assist public health promotion to raise awareness regarding sun protection and skin cancers in the region by targeting commonly used terms for each geographical location.